Anatomy of the vesicovaginal fascia and its relation to branches of the inferior hypogastric plexus. Issue 7 (2nd April 2022) - Stupart, Douglas; Pickles, Kylie; Briggs, Chris
Abstract: The inferior hypogastric plexus (IHP) lies in the extraperitoneal pelvis, and supplies branches to pelvic and perineal viscera. In men, the rectoprostatic fascia (Denonvillier's fascia) forms a distinct double fascial layer between the seminal glands and the rectum. The hypogastric nerve projections to the prostate and seminal glands run anterior to this. An analagous fascial layer in women between the vagina and cervix posteriorly and the urinary bladder anteriorly has recently been described. The purpose of this study was to examine the anatomy of the vesicovaginal fascia (VVF) and to determine its relationship to the anterior branches of the IHP. This dissection study examined the fascial layers between the posterior urinary bladder and anterior vagina/cervix (VVF) in 15 female embalmed cadavers and three fresh specimens. Anterior branches of the IHP were identified and followed distally. The relationship between these nerve projections and the VVF was examined. In 16 dissection, the VVF was identified as a complete fascial plane extending beneath the vesicouterine pouch to the neck of the bladder inferiorly and to the endopelvic fascia laterally. Anterior projections from the hypogastric nerves and IHP maintained an extraperitoneal course passing anteriorly to the VVF towards the urinary bladder The VVF is a distinct fascial structure and projections of the hypogastric nerves pass anterior to this. This may have implications for nerve sparing hysterectomy.